Популістський дискурс та політична мобілізація - Возняк, Ярина (Видавництво Львівської політехніки, 2017)
This article moves toward understanding the communicative peculiarities of two mutually strengthening social phenomena in contemporary democracies – populism and political mobilization. Populism is to be reconceptualized in political sociology through populist mobilization, shifting research from intuition to practice.
Keywords: популізм; дискурс; риторика; політична стратегія; політична мобілізація; популістська мобілізація